TRANSLATION OF SOCIAL CITIZENSHIP TO ARCHITECTURE & BUILT ENVIRONMENT: A METHODOLOGICAL REVIEW - Ismail, Mohd Noorizhar; Sapian, Abdul Razak; Scriver, Peter; Rashid, Mizanur (PLANNING MALAYSIA, 2017)
Social Citizenship is a concept that is used to represent acceptance and identity by the local community. This is a manifestation expressed in the form of space, monument or buildings. Buildings such as mosques and other religious buildings are a form of manifestation to such expression left for other generations to see and study. This manifestation of citizenship through religious buildings can be an expression of struggle, establishment, sense of belonging and local acceptance towards achieving social citizenship. The understanding of this concept implicitly shows that these elements are the driving forces behind the architecture that is erected in order to find approval from the local population. This paper reviews the employed research designs, methods and procedures in the process of understanding the translation of social citizenship to architecture expressed by mosques. The methods adopted were aimed toward obtaining archival/historical evidence that can elicit proof of the concept. The methods also involved the process of inquiry that would be the basis for discussion and to draw a conclusion to the relationship between social citizenship and architecture. This paper also highlights the strengths and limitations of the methodological techniques besides spelling out the variables needed to prove the relationship.